Bumiputra entrepreneurs’ perception and propensity to sustainable entrepreneurship / Wei-Loon Koe, Roaimah Omar and Izaidin Abdul Majid - Wei-Loon, Koe (Division of Research and Industry Linkages , UiTM Melaka, 2014)
Islam emphasizes on making a living through entrepreneurship and also conserving natural capital. The Islamic teaching is very much related to sustainable entrepreneurship. As an Islamic country, there is a great number of Muslims living in Malaysia. However, how Muslim entrepreneurs perceive sustainable entrepreneurship still remains unknown. As such, this study was conducted to examine the influence of Bumiputra entrepreneurs’ perceptions on the propensity to sustainable entrepreneurship. Based on the questionnaire survey conducted on 242 randomly selected Bumiputra entrepreneurs in Malaysia, the results concluded that perceived desirability and perceived feasibility significantly and positively influenced their propensity to sustainable entrepreneurship. The findings have shed some light on the importance of perception in promoting sustainable entrepreneurship. Suggestions for future researchers have also been put forth.